Fabrication, properties and in vitro study of Magnesium/ Zinc/ Bioglass composite fabricated by powder metallurgy method - Noorazimah, Mohd Ab Llah (Universiti Malaysia Perlis (UniMAP), 2016)
Doctor of Philosophy in Materials Engineering